Novel neck cold compress bag - SHI ZHONGNA; GAO QIN; XU WENHUA (2012)
The utility model provides a novel neck cold compress bag, which comprises a left ice bag area and a right ice bag area, wherein one end of each ice bag area is connected with a head area, one end of the head area is provided with a head snap fastener, the other end of each ice bag area is connected with a submaxillary cloth bag area, one end of the submaxillary cloth bag area is provided with a submaxillary area snap fastener, head fixing strap snap fasteners are arranged corresponding to the head snap fastener, and a head fixing strap is arranged between the two head fixing strap snap fasteners; the included angle alpha of double sides of the submaxillary cloth bag area is 55 to 65 degrees; the included angle beta 1 between the upper parts of the head area and each ice bag area is 115 to 125 degrees, the included angle beta 2 between the lower parts of the head area and each ice bag area is 45 to 55 degrees, and the upper left included angle gamma of the head area is 95 to 105 degrees; and the middle of the